THE EFFECT OF GIVING INSTANT NOODLES PATETA (CATFISH, TEMPEH FLOUR, AND TAPIOCA FLOUR) ON BODY WEIGHT OF UNDERWEIGHT TODDLERS - Aisyah, Salsabila; Podojoyo, Podojoyo; Mardiana, Mardiana; Yulianto, Yulianto; Sartono, Sartono (Jurnal Gizi dan Pangan Soedirman, 2025)
Underweight remains one of the most common nutritional problems among toddlers, characterized by body weight that does not meet age standards due to inadequate nutrient intake. One effort to help meet toddlers’ nutritional needs is through the provision of supplementary food (PMT) in the form of instant noodles made from catfish, tempeh flour, and tapioca flour. This study aims to determine the effect of instant noodles based on catfish, tempeh flour, and tapioca flour on the body weight of underweight toddlers at Makrayu Public Health Center. A quasi-experimental method with a pre-test and post-test control group design was used. The study was conducted over 21 days with a total sample of 59 toddlers aged 24–59 months, selected using simple random sampling. The participants were divided into two groups: 29 toddlers in the treatment group and 30 toddlers in the control group. The results showed that the treatment group experienced an average weight gain of 0.3983 kg, while the control group showed an average gain of 0.2033 kg. Statistical analysis using independent t-test indicated a significant effect of the instant noodles on weight gain among underweight toddlers at Makrayu Health Center (p-value = 0.002).